2011
DOI: 10.1111/j.1476-5381.2010.01168.x
|View full text |Cite
|
Sign up to set email alerts
|

Low dose of the liver X receptor agonist, AZ876, reduces atherosclerosis in APOE*3Leiden mice without affecting liver or plasma triglyceride levels

Abstract: BACKGROUND AND PURPOSELiver X receptor (LXR) agonists are atheroprotective but often induce hypertriglyceridaemia and liver steatosis. We investigated the effect of a novel high-affinity LXR activator, AZ876, on plasma lipids, inflammation and atherosclerosis, and compared the effects with another LXR agonist, GW3965. ) for 20 weeks. Total cholesterol and triglyceride levels were measured using commercial kits. Plasma cytokines were determined by using bead-based multiplex suspension array kits with the Lumine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…Sitosterol and campesterol were extracted from plasma and analyzed by gas chromatography (GC)/MS (22). 7␣-hydroxy-4-cholesten-3-one (C4) was extracted from plasma and analyzed using liquid chromatography/MS/MS (23).…”
Section: Biochemical Analysismentioning
confidence: 99%
“…Sitosterol and campesterol were extracted from plasma and analyzed by gas chromatography (GC)/MS (22). 7␣-hydroxy-4-cholesten-3-one (C4) was extracted from plasma and analyzed using liquid chromatography/MS/MS (23).…”
Section: Biochemical Analysismentioning
confidence: 99%
“…Because of the double-edged role of LXRa in the vascular and hepatic systems, only selective agonists or antagonists of this nuclear receptor have the potential for development as therapeutics. Recent studies have suggested that selective regulation of LXRa in target tissues may be applied to the treatment of many diseases, including metabolic syndromes [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…LXRα is primarily expressed in the liver, intestine, adipose tissue, and macrophages, whereas LXRβ is expressed ubiquitously (43). Similar to ER, LXR activation reduces the development of atherosclerosis despite modest changes in plasma lipoprotein levels (44), suggesting that the underlying mechanism(s) may involve direct effects on vascular cell functions. Oxysterols such as 22(R)-hydroxycholesterol and 24(S)-hydroxycholesterol are major endogenous LXR ligands.…”
Section: Er Modulation By Oxysterols Through Lxr Activationmentioning
confidence: 99%